Maternal Microchimerism in Hirschsprung’s Disease - Kiefer, Autumn S.; Lang, Tara R.; Hein, Molly S.; McNallan, Kelly T.; Moir, Christopher R.; Reed, Ann M. (American Journal of Perinatology, 2012)
Hirschsprung’s disease (HD) presents with severe constipation due to absent ganglion cells in the distal rectum. We sought to determine whether maternal chimeric cells are present in aganglionic bowel. We hypothesize that chimeric cells are part of the unfavorable microenvironment that leads to the destruction of enteric neurons in HD. Intestinal biopsies and resections from seven male patients with HD were compared with four male patients with chronic constipation and six with bowel atresia. Fluorescence in situ hybridization was used to identify chimeric cells based on male/female (XX/XY) differences. The location and immunophenotype of chimeric cells were also studied. Chimeric cells were present more often in the small intestine and rectum, compared with the appendix and colon. Patients with HD had a greater number of chimeric cells per 10× magnification field than patients with chronic constipation or congenital atresia. Chimeric cells were predominantly in the submucosa and outer longitudinal muscle layer in HD. Immunophenotyping identified over 40% of chimeric cells as inflammatory. Chimeric cells are present in greater numbers in aganglionic bowel than in other disorders. Clustering of chimeric cells in areas of absent ganglia lends support to the proposed role of maternal microchimerism in allo-autoimmune responses.
Keywords: Hirschsprung’s disease; microchimerism; intestinal atresia; chimerism